2022
DOI: 10.3390/v14030602
|View full text |Cite
|
Sign up to set email alerts
|

Hallmarks of Metabolic Reprogramming and Their Role in Viral Pathogenesis

Abstract: Metabolic reprogramming is a hallmark of cancer and has proven to be critical in viral infections. Metabolic reprogramming provides the cell with energy and biomass for large-scale biosynthesis. Based on studies of the cellular changes that contribute to metabolic reprogramming, seven main hallmarks can be identified: (1) increased glycolysis and lactic acid, (2) increased glutaminolysis, (3) increased pentose phosphate pathway, (4) mitochondrial changes, (5) increased lipid metabolism, (6) changes in amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 286 publications
(328 reference statements)
1
30
0
Order By: Relevance
“…Recently, it has been shown that metabolic reprogramming due to viruses’ infection can result in increased glycolysis and decreased TCA cycle and increases the production of advanced glycation end-products (AGEs) [ 46 ]. AGES can be formed spontaneously from increased glycolytic intermediates and oxidative stress [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been shown that metabolic reprogramming due to viruses’ infection can result in increased glycolysis and decreased TCA cycle and increases the production of advanced glycation end-products (AGEs) [ 46 ]. AGES can be formed spontaneously from increased glycolytic intermediates and oxidative stress [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…We also demonstrated that the viral proteins alter the glycolysis pathway resulting in increased glycolytic intermediates and decreased pyruvate. This phenomenon has a precedent where viruses use this pathway to replicate [ 46 ]. Studies showed that HCV deregulates the mitochondria, promotes HIF-1α, and activates the glycolysis pathway [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the climbing behaviour of infected larvae was increased by glucose supplementation, and inhibited by insulin treatment, DCA or 2-DG treatment, and dietary restriction, confirming that reduced metabolic activity impeded climbing behaviour. Inhibition of the TCA cycle with DCA had more dramatic effects on HearNPV loads and climbing behaviour compared with inhibition of glycolysis with 2-DG, probably reflecting the greater importance of the TCA cycle in supplying cellular energy (Allen et al, 2022), which is critical for insect locomotion (Hassan et al, 2021). The full set of treatments and observed responses is summarized schematically in Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…Like cellular miRNAs, v-miRNAs can target and regulate viral gene expression (including cellular gene expression) to modulate the active and latent switch modes. Maintenance of the viral latent phase is key to viral immune evasion and v-miRNAs are active participants in this process (reviewed in [ 168 ]). For example, EBV BART miRNAs play a significant role in controlling the viral life cycle, and thus maintaining latency.…”
Section: Persistent Viral Infection and Oncogenesis: V-mirnas As Effe...mentioning
confidence: 99%